Bentuk Penyajian Tari Hari Langsung Sebagai Tari Kreasi Masyarakat Kota Pekanbaru - Rahayu Febri Armi; Herlinda Mansyur (FBS Universitas Negeri Padang, 2022)
This research aims to describe and reveal the form of presentation of Tari Hari Lansung as a Dance Creation of Pekanbaru City Community. This type of research is qualitative using descriptive methods. Research instruments are researchers themselves and are assisted by supporting instruments such as stationery, cameras and mobile phones. This type of data uses primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are collecting data, describing data and inferring data. The results showed that Hari Langsung dance is a creation dance that tells the traditional procession of Riau Malay marriage, although this dance has to do with the traditional procession of marriage, but does not show the marriage in general. This Tari Hari Lansung there are 5 procession, namely arak-arak an, silat, doorstop, reciprocated pantun and side by side. This Tari Hari Lansung is danced in groups with 12 male dancers. The properties used in The Direct Day dance are kompang, turmeric rice, umbrella, uncang, selayar, wedding edit, doorstop cloth. Costume dancers of Hari Langsung Dance using the caged bay brackets, the head uses kopiah given a brooch as an accecoris, and uses malay songket cloth. Musical instruments used are compang, acordion, violin, gambus, long drum and vocals.